2013
DOI: 10.2516/ogst/2013135
|View full text |Cite
|
Sign up to set email alerts
|

Development of a General Modelling Methodology for Vacuum Residue Hydroconversion

Abstract: Re´sume´-De´veloppement d'une me´thodologie ge´ne´rale de mode´lisation pour l'hydroconversion de re´sidu sous vide -Ce travail porte sur le de´veloppement d'une me´thodologie de mode´lisation cine´tique de proce´de´s de raffinage, et plus particulie`rement de proce´de´s pour la conversion de re´sidus sous vide. L'approche propose´e permet de surmonter le manque de de´tail mole´culaire des fractions pe´trolie`res et de simuler la transformation des mole´cules de la charge en mole´cules de l'effluent au moyen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The different probability density distribution functions were selected according to the structural properties of the different components. The result confirmed that the simulation error met the requirements. Zhang et al added structural information analyzed by high-resolution mass spectrometry (HRMS) to the construction of a compositional model of residual oil containing 400,000 molecules. Their results demonstrated that their model could significantly reduce the deviation between simulated and experimental values .…”
Section: Introductionmentioning
confidence: 69%
“…The different probability density distribution functions were selected according to the structural properties of the different components. The result confirmed that the simulation error met the requirements. Zhang et al added structural information analyzed by high-resolution mass spectrometry (HRMS) to the construction of a compositional model of residual oil containing 400,000 molecules. Their results demonstrated that their model could significantly reduce the deviation between simulated and experimental values .…”
Section: Introductionmentioning
confidence: 69%
“…The slight deviations from the deterministic solution in various sections along the reactor are caused by the inherent random noise of stochastic simulation methods. Such divergences can be corrected by averaging repeated stochastic simulations, as pointed out by de Oliveira et al 50 Therefore, multiple repetitions of the hydrocracker simulations were required in order to eliminate any defects associated with the simulation method. 4.2.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant data especially for the heavy components is very scarce. Monte Carlo method has been applied by a number of authors to develop component sets having proper properties and reaction networks with usable kinetics. Nevertheless, the positive aspect is that the data concerning real components’ properties and their reactions are not bound to a single system as is the case with lumped components, but once collected and stored to a databank, they can be utilized for handling new cases. Some models accounting for molecular structure have been published, e.g., for gasoil hydrotreating, for fluid catalytic cracker, , and for hydrotreating of light cycle oil from fluid catalytic cracking and hydrocracking of vacuum residues .…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…However, the architecture of the model is not dependent on the method used for generation of the feed composition and properties. An alternative approach for feed composition generation would be the Monte Carlo methods presented in the literature. ,− …”
Section: Description Of the Modelmentioning
confidence: 99%